HISTORY OF ARABIC CURRICULUM DEVELOPMENT IN INDONESIA - faizin, khoirul; ismail, ismail (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2023)
first curriculum was compiled until the latest curriculum in 2020, known as the "MERDEKA BELAJAR"curriculum. This study uses the method of literature review by taking data from the literature related to the research problem. References to this study come from books, scientific articles and some other research results. The source of the data obtained is prepared based on the results of the study of the information obtained. In this study it was found that the Arabic language has undergone many developments since it was taught until now. In each period of the curriculum, the Arabic language has a distinctive style that adapts to the existing curriculum. This research is expected to be a new finding that can be a reference for making policies in implementing the Arabic curriculum.